Multi-Channel System for Sound Creation in Open Areas - Andrzej GOŁAŚ; Katarzyna SUDER-DĘBSKA (Archives of Acoustics)
There are typically two systems in use for sound reinforcement in open areas: the central, “wall of sound” system with speakers localized at the sides of the stage, and the zone system, in which additional speakers are introduced to obtain a uniform sound pressure level throughout the area of listening. In the past two decades the line array systems gained great popularity. The main purpose of their use is to obtain a uniformly distributed sound level throughout the listening area in order to achieve good speech intelligibility. The present paper aims to present an alternative and original method of sound reinforcement in open areas which is in contrast to the above solutions. This new method allows achieving a uniformly distributed sound pressure and good speech intelligibility in the area of interest, and also allows to gain spatial sound impression that accompanies sound reproduction in concert halls. Another advantage of the proposed system is the reduction of the sound level outside the area of interest, i.e. reduction of the noise level outside the area of listening.